Penerapan Strategi Bisnis Berkelanjutan Sesuai Dengan Prinsip Syariah Di Dhuafa Mart - Hasda, Mifta; Winario, Mohd; Hidayat, Hidayat; Zaim, Muhammad (Journal of Community Service and Empowerment, 2024)
This community service aims to integrate sharia principles into sustainable business strategies to improve operational sustainability and social impact of Dhuafa Mart. The methods used include needs analysis, strategy design, training, implementation, and evaluation and adjustment. The initial needs analysis identified challenges and opportunities in existing business practices, while strategy design involved developing a plan that combined sharia principles with sustainable business practices. Training and socialization were conducted to ensure staff understanding and skills in implementing the new strategy. Implementation was carried out in stages to minimize disruption, followed by monitoring and evaluation to ensure the effectiveness and suitability of the strategy. The results of the community service showed that the strategies implemented succeeded in improving operational efficiency, strengthening customer relationships, and providing significant social benefits, including empowering the data community and protecting the environment. In conclusion, integrating sharia principles into sustainable business has proven effective. It can be used as a model for other companies, offering ethical and sustainable solutions in the context of modern business.